FACTORS AFFECTING CONSUMERS IN USING SERVICES J&T EXPRESS (CASE STUDY ON J&T EXPRESS BRANCH MARGONDA DEPOK) - Helen Aldila Saputri; Widyo Nugroho (AIBPM Publisher, 2018)
J&T Express is one of the companies engaged in the provision of logistics services in the form of delivery of documents and goods that can compete with senior companies. One marketing strategy undertaken by a J&T Express company is to use a Brand Ambassador as part of advertising, where other similar companies do not use brand ambassadors as a means of promotion. Maintaining the quality of service also becomes one part of the strategy that companies do in the face of competition. The decision of prospective users of logistic services also has another factor as an indicator of the selection of logistics service providers, is price. In this study discussed three dependent variables that affect consumer decisions in using J&T express services consisting of Brand Ambassador, Service Quality, and Price. This research will be carried out by spreading 200 questionnaires to consumers who use the services of J&T Express Branch Margonda Depok. Technique done using technique of Multiple Linear Regression, Analysis using SPSS analysis tool 23. The result of research proves that three variables namely Brand Ambassador, Service Quality, and Price partially influence to consumer decision in using services of J&T Express Branch Margonda Depok. And simultaneously there is a positive influence between independent variables namely Brand Ambassador variable, Service Quality and Price to the dependent variable that is consumer decision. It is seen that the relationship between Brand Ambassador variable, Service quality, and Price on Consumer Decision is quite strong, that is R = 0,634 or equal to 63,4%